2012
DOI: 10.1371/journal.pone.0036869
|View full text |Cite
|
Sign up to set email alerts
|

Complete Chloroplast Genome Sequence of a Major Invasive Species, Crofton Weed (Ageratina adenophora)

Abstract: BackgroundCrofton weed (Ageratina adenophora) is one of the most hazardous invasive plant species, which causes serious economic losses and environmental damages worldwide. However, the sequence resource and genome information of A. adenophora are rather limited, making phylogenetic identification and evolutionary studies very difficult. Here, we report the complete sequence of the A. adenophora chloroplast (cp) genome based on Illumina sequencing.Methodology/Principal FindingsThe A. adenophora cp genome is 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
203
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(248 citation statements)
references
References 55 publications
(60 reference statements)
42
203
0
Order By: Relevance
“…3a). The number of tandem repeats in Chuanminshen cp genome was equivalent to that of crofton weed (Nie et al 2012) and slightly more than bamboo (Zhang et al 2011) whereas the longest tandem repeat size was shorter than the crofton weed with 85 bp and bamboo with 65 bp. To investigate the dispersed repeats in Chuanminshen cp genome, we adjusted the setting parameters of the REPuter described above.…”
Section: Cp Genome General Features Of Chuanminshenmentioning
confidence: 88%
“…3a). The number of tandem repeats in Chuanminshen cp genome was equivalent to that of crofton weed (Nie et al 2012) and slightly more than bamboo (Zhang et al 2011) whereas the longest tandem repeat size was shorter than the crofton weed with 85 bp and bamboo with 65 bp. To investigate the dispersed repeats in Chuanminshen cp genome, we adjusted the setting parameters of the REPuter described above.…”
Section: Cp Genome General Features Of Chuanminshenmentioning
confidence: 88%
“…With the emergence and development of high-throughput sequencing technology, more and more chloroplast genomes of Asteraceae species have been dissected recently (Nie et al 2012;Liu et al 2013;Bock et al 2014). The available completed genomes provide an opportunity to perform comparative analysis within these members of Asteraceae family at the whole chloroplast genome level.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple sequence alignment between six Fritillaria genomes indicated that the IR regions were more conserved than the LSC and SSC regions due to copy correction by gene conversion in IR regions [39]. The most divergent regions were found in IGSs, which have been used in phylogenetic studies [9,28]. For the coding regions, the most divergent regions included matK, rpoC1, rpoC2, ycf1, ycf2, ndhD, and ndhF.…”
Section: Discussionmentioning
confidence: 99%
“…Chloroplast genomes provide genomic resources for phylogenetic analysis, and many studies have used protein-coding sequences or whole chloroplast genome sequences [6,28,41]. We used ML and MP analysis to construct a phylogenetic tree focusing on Fritillaria species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation